Deformation behavior of aluminum-silicon (Al-Si) alloy during forging under various processing conditions - Khemraj; Jha A.K.; Ojha S.N. (My University, 2025)
The feasibility of bulk processing (forging) of aluminum-silicon alloy under warm and cold conditions is demonstrated in the present work. The results show that, in closed-die forging the metal deformation is uniform with no surface defects whereas in case of open-die forging the cracks gets developed during deformation process. Mechanical and metallurgical properties such as hardness, wear resistance, and microstructure also get improved during the forging process. The primary silicon size decreases after forging, therefore the morphology and distributions of primary and eutectic silicon were changed. © 2018 Elsevier Ltd.